DAMPAK PENGGUNAAN GADGET TERHADAP SIKAP SOSIAL DAN PERILAKU BELAJAR SISWA SDI UNGGULAN BTN PEMDA KOTA MAKASSAR - Deya Idayani; Nursalam; Muhlis Madani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
This research was attempted as a more methodical critique maneuver to look at the use of gadgets in terms of their influence on social attitudes and student learning behavior as well as the factors that allow both of them to be discussed further. This qualitative research with a phenomenological approach relies on the quality of the data that has been collected using standard qualitative research instruments, namely observation, interviews, as well as documentation and encryption of the results of the interviews as primary data sources. Six of the respondents were students of grades IV, V, and VI; three teachers of the same class and three guardians of students were also involved, so the total sample size was 12 people. The findings show that there are various negative and positive impacts in terms of the use of gadgets on social attitudes and student learning behavior, as well as potential factors that also influence them which have contributions and influence characteristics that tend to differ between variables.